Genetic and non-genetic factors affecting calf survivability in Gir crossbreds - MOTE, MAHENDRA GORAKH (Indian Journal of Dairy Science, 2023)
Data on survivability traits of Gir crossbred calves, maintained at RCDP on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri, Maharashtra was collected for a period of 15 years (2005-2019) to study effect of genetic and non-genetic factors on survivability traits of calf. Traits studied were survivability at day 0-3, 4-15, 16-30, 3-90, 91-180 and 181-365 days. To determine the effects of genetic and non-genetic factors on survivability traits, least squares analysis of variance (Harvey, 1990) was applied, considering the fixed effects like genetic group, season and period of birth, parity of dam and birth weight of calves. The least square means of survivability per cent of Gir crossbred calves at 0-3, 4-15, 16-30, 31-90, 91-180 and 181-365 days were 96.17±0.80, 86.17±2.12, 89.23±2.03, 80.39±2.89, 83.41±3.02 and 95.61±1.79 per cent, respectively. The significant (P<0.05) effect of period of birth was found on calf survivability trait at different ages viz. days 31-90 and days 181-365. Parity of dam had non-significant effect on calf survivability traits of the Gir crossbred calves. Significant (P<0.05) effect of season of birth on calf survivability was observed only at 0-3 days age survivability trait. Significant (P<0.05) effect of sex of calves on survivability traits was recorded at 0-3, 4-15, 16-30 and 31-90 days. In the present study, birth weight of calf had significant (P<0.01) effect on calf survivability at 0-3 days after birth. The non-significant effect was reported among the survivability patterns of calves with different genetic groups.